The Role of Silicates in Interstitial Lung Disease - Leyva Hurtado, Francisco José (2007)
Interstitial Lung disease (ILD), produces disruption of alveolar walls with loss of functionality and accumulation of scar tissue. Asbestosis and silicosis are the ILD produced by the inhalation of asbestos fibers or silica particles respectively. An increase in prostacyclin release after exposing endothelial cells to asbestos has been reported. This study attempts to elucidate the role of lung epithelial cells in the generation of asbestos induced ILD. A cell model to study crocidolite-induced toxicity was developed using LA-4 cells, previously characterized as alveolar type II cells. LA-4 cells when exposed to crocidolite had a decrease in viability and an increase in the release of LDH and 6-keto PGF1α, a prostacyclin metabolite. Prostacyclin release was Cox 2 and vitronectin receptor (VNR) mediated. Coating crocidolite asbestos with vitronectin enhances its internalization via VNR, which also recognize the Arg-Gly-Asp (RGD) motif present in a variety of ligands (e.g., vitronectin, fibronectin). These findings propose that crocidolite is coated by an RGD protein and binds VNR inducing Cox 2 expression promoting prostacyclin release. Cytotoxicity did not follow the same model. In silica studies, it has been previously reported that Scavenger receptor A I/II (SR-A I/II) plays a role in silicainduced apoptosis. The cytoplasmic domain of the SR-AI/II has four aminoacids: Ser25, Ser32, Ser53, Thr34 that can be phosphorylated, and the extracellular region contains a lysine-rich cluster that is required for Acetylated Low density lipoprotein (AcLDL) binding. SR-AI contains a cysteine-rich domain, which is absent in SR-AII. This study evaluated the role of the four aminoacids that could be phosphorylated, and differences between SR-AI and SR-AII in silica binding. Constructs expressing SR-AII, and mutated SR-AIIs containing deletions to Ser25, Ser32, Ser53, Thr34 and KE (lysine cluster) were generated and CHO cells were transfected. Receptor functionality was verified by AcLDL uptake. Silica binding or silica-induced apoptosis was not statistically significant different from transfected controls. In addition, no statistically significant difference was found between SR-AI and SR-AII in AcLDL uptake, silica binding, and silica-induced apoptosis. This study shows that asbestos or silica alone cannot induce its effect, and asbestos required to be coated by RGD proteins.